Analisis Kesalahan Konsep Pembelajaran Pada Materi Pesawat Sederhana di Sekolah Dasar - Atika Aprilia; M Irdan Jundi Arrosyid; Nur Hasijazh; Wahyu Kurniawati (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to find out conceptual errors in simple airplane material in elementary schools. Understanding concepts is the most important aspect in learning simple airplanes. This is to avoid students' learning misconceptions and is one of the conditions for achieving success in learning simple airplanes. This research is descriptive research with a qualitative approach. The data collection procedure carried out in this research is a literature study. Data analysis techniques include data reduction, data presentation, and conclusions. The research results show that the factors causing students to experience conceptual errors include students' lack of knowledge, wrong or incomplete intuition, teachers' lack of mastery of the material, teachers' use of textbooks, and monotonous teaching methods.